Study on the effects of Zhuanggu Guanjie Pill, a modern Chinese medicine formula, on the activities and mRNA expression of seven CYP isozymes in rats. (5th December 2021) - Chai, Yuanyuan; Xu, Yunxia; Xia, Ziyin; Huang, Xin; Zhang, Luyong; Jiang, Zhenzhou
Abstract: Ethnopharmacological relevance: Zhuanggu Guanjie Pill (ZGGJP), a modern Chinese medicine formula, is composed of 12 herbs and has been used to treat osteoporosis in China for almost 30 years. However, no in vivo study of the influences of ZGGJP on the cytochrome P450 (CYP) activities have been reported. Aim of the study: The aim of this study was to evaluate the effects of ZGGJP on the activities and the mRNA expression of CYP enzymes (CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A) and their corresponding nuclear receptor levels in rats. Materials and methods: After 7 days oral treatment of ZGGJP at low- and high-dose, cocktail solution was given to rats. Blood samples were collected at series of time points. The plasma concentrations of probe drugs and their corresponding metabolites were determined by UPLC-MS/MS. The influence of ZGGJP on the activities of seven CYPs were evaluated the metabolic ratios (Cmax and AUC0-t) for metabolites/probe drugs. In addition, the effects of ZGGJP on the mRNA expression of CYPs and their corresponding nuclear receptors in rat liver were evaluated by real-time PCR. Results: ZGGJP showed significant inductive effects on CYP1A2 and CYP2B6 of both male and female rats. The influence of ZGGJP on CYP2C9 and CYP3A showed gender difference. ZGGJP could induce the activities of CYP2C9 and CYP3A in female rats, but have no influence on the activities in male rats. ZGGJP had no effects on CYP2D6, CYP2C19 and CYP2E1. The mRNA expression results of CYPs were in accordance with the pharmacokinetic results. The mRNA expression levels of constitutive androstane receptor (CAR) and vitamin D receptor (VDR) were increased significantly in female rats at high dosage, but no significant changes were observed in male rats. Conclusion: ZGGJP had inductive effects on CYP1A2 and CYP2B6 in both male and female rats. The results showed that ZGGJP could induce the activities of CYP2C9 and CYP3A in female rats, but had no effect in male rats. This may suggest that the influence of ZGGJP on CYP2C9 and CYP3A exhibit gender difference. The inductive effects of ZGGJP on the activities of CYPs, exhibiting gender difference, may be regulated by CAR and VDR. Therefore, co-administration of ZGGJP with other drugs, especially using CYP2C9 and CYP3A substrates in females, may need dose adjustment to avoid herb-drug interaction. Graphical abstract: Image 1 Highlights: It was found that ZGGJP showed inductive effect on CYP1A2 and CYP2B6. ZGGJP could induce the activities of CYP2C9 and CYP3A in female rats. The inductive effects of ZGGJP on the activities of CYPs may be regulated by CAR and VDR.